2011
DOI: 10.1038/ki.2011.188
|View full text |Cite
|
Sign up to set email alerts
|

High doses of epoetin do not lower mortality and cardiovascular risk among elderly hemodialysis patients with diabetes

Abstract: Summary Background Whether exposure to high erythropoiesis-stimulating agents (ESA) doses results in adverse cardiovascular outcomes in hemodialysis patients based on the presence of diabetes has been suggested by an earlier randomized trial but remains inconclusive. Methods Data from the US Renal Data System were used to identify 35,593 Medicare patients on hemodialysis: 19,034 (53%) were diabetic. We fit a pooled logistic model to estimate the probability of mortality and a composite cardiovascular end po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 24 publications
4
36
0
Order By: Relevance
“…Hirai et al reported that the dose of CERA could be reduced throughout the 28-week observation period by switching EPO to once-every-4-week CERA administration [19]. This is similar to our finding.…”
Section: Discussionsupporting
confidence: 83%
“…Hirai et al reported that the dose of CERA could be reduced throughout the 28-week observation period by switching EPO to once-every-4-week CERA administration [19]. This is similar to our finding.…”
Section: Discussionsupporting
confidence: 83%
“…Safety concerns were raised during treatment of anemia in diabetic patients with CKD when they showed a twofold higher risk of stroke, an increased risk of venous thromboembolism and cancer-related deaths (210). Several studies have suggested that exposure to high doses of Epo mimetics, when needed to achieve higher hemoglobin levels, is harmful and explains this phenomenon (211,212). Very high doses of Epo, in conjunction with hypoxia, has also been associated with a paradoxical neurotoxic effect suggesting dose-response conditions need to be optimized.…”
Section: Epo In Treatment Of Cardiovascular Diseasesmentioning
confidence: 99%
“…Targeting a higher hemoglobin level over a prolonged period has been shown to increase the risk of cardiovascular events and death in stable outpatients and is cause for concern. [6][7][8][9][10][11] In a well-conducted randomized controlled trial, Singh et al 10 showed that in patients with chronic kidney disease not on dialysis therapy, those with a higher targeted hemoglobin level (135 g/L) have a 34% increased risk of a composite event of death, myocardial infarction, hospitalization for congestive heart failure, and stroke. In another randomized trial, assignment to a higher targeted hemoglobin level (130 g/L) nearly doubled the risk of a stroke.…”
Section: Discussionmentioning
confidence: 98%
“…This may increase the risk of cardiovascular events, vascular access thrombosis, and possibly mortality in HD patients because previous studies have shown adverse outcomes in patients with higher targeted hemoglobin levels over a prolonged period. [6][7][8][9][10][11] Individuals with erythropoietin hyporesponsiveness appear to be at particular risk. 9,12,13 Given the lack of demonstrated benefit and the potential for increased risk of adverse events, we sought to determine whether increasing the ESA dose in HD patients during the first 14 days of hospitalization is associated with increased risk of exceeding recommended hemoglobin targets.…”
mentioning
confidence: 95%